Evaluating the residual stress in PbTiO3 thin films prepared by a polymeric chemical method - Valim, D.; Souza, A. G.; Freire, PTC; Mendes, J.; Guarany, C. A.; Reis, R. N.; Araujo, E. B. (Iop Publishing Ltd, 2004)
We report a study of residual stress in PbTiO3 (PT) thin films prepared on Si substrates by a polymeric chemical method. The E(1TO) frequency was used to evaluate the residual stress through an empirical equation available for bulk PT. We find that the residual stress in PT films increases as the film thickness decreases and conclude that it originates essentially from the contributions of extrinsic and intrinsic factors. Polarized Raman experiments showed that the PT films prepared by a polymeric chemical method are somewhat a-domain (polar axis c parallel to the substrate) oriented.